2013
DOI: 10.1093/bja/aet103
|View full text |Cite
|
Sign up to set email alerts
|

Distinct long-term neurocognitive outcomes after equipotent sevoflurane or isoflurane anaesthesia in immature rats

Abstract: Both isoflurane and sevoflurane delivered at 1 MAC for 4 h to immature rats caused a deficit in long-term memory. Isoflurane also caused a deficit in short-term memory. Isoflurane might be more detrimental than sevoflurane in very young animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 29 publications
8
37
0
Order By: Relevance
“…This is consistent with Zhu and colleagues’ finding that adult rats and mice that received 35 minutes of 1.7% isoflurane daily, for five consecutive days, from postnatal day 14 were cognitively impaired in comparison to control group [25]. The same cognitive impairment was also observed in rats that had single 4-h exposure to isoflurane [22]. The cognitive impairment seems to be correlated with persistent decrease in the hippocampal neural stem cell pool and neurogenesis [25].…”
Section: New Evidence On Anaesthetics Induced Neuronal Cell Death supporting
confidence: 90%
“…This is consistent with Zhu and colleagues’ finding that adult rats and mice that received 35 minutes of 1.7% isoflurane daily, for five consecutive days, from postnatal day 14 were cognitively impaired in comparison to control group [25]. The same cognitive impairment was also observed in rats that had single 4-h exposure to isoflurane [22]. The cognitive impairment seems to be correlated with persistent decrease in the hippocampal neural stem cell pool and neurogenesis [25].…”
Section: New Evidence On Anaesthetics Induced Neuronal Cell Death supporting
confidence: 90%
“…However, increasing experimental data in neonatal rodents and nonhuman primates settings have shown that early exposure to commonly used general anesthetics impaired brain development such as inhibiting neurogenesis, inducing widespread neuroapoptosis and longterm neurocognitive deficits [1][2][3]. Epidemiological studies indicated that young children underwent general anesthesia were possibly associated with potential neurocognitive impairment later in life [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous animal experiments have documented neuronal death following exposure to volatile anesthetics 4,6,7 . In addition, factors influencing cell death have been researched extensively, including duration of anesthesia and the specific anesthetic agent that is delivered 6,8,9 . Various mechanisms have even been proposed to account for the process of anesthetic-induced neuroapoptosis 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Cell death occurs acutely in the period immediately following anesthesia 4,8,21 , and the thalamus and hippocampus are areas known to be susceptible to extensive neurodegeneration 4,7,21 . Long-term behavior is separately assessed in adolescence or adulthood using a range of tasks 4,6,7,9 .…”
Section: Introductionmentioning
confidence: 99%